IMPLEMENTASI KEBIJAKAN DALAM UPAYA MENGATASI DAN MENCEGAH PENYEBARAN WABAH PMK DAN LSDV OLEH BPTUHPT PADANG MENGATAS - Erman Syarif; Roni Ekha Putera (Halu Oleo University, 2024)
This study aims to analyze the implementation of FMD and LSDV prevention policies by BPTUHPT Padang Mengatas, West Sumatra Province. The method used in this research is a qualitative method to see how the implementation of FMD and LSDV outbreak prevention policies. Data collection was carried out using interviews, observation, and documentation. Data analysis was carried out using triangulation techniques, namely data reduction, data presentation, and conclusion drawing. The results showed that the implementation of FMD and LSDV outbreak prevention policies at BPTU HPT Padang Mengatas was well implemented. Supported by adequate resources, facilities, and infrastructure for supporting the FMD and LSDV prevention processes. The bureaucratic structure is well implemented in formulating policies and in their implementation in the field, which is in accordance with the qualifications of employees who are experts in their fields. The communication process for providing information about standard procedures for preventing FMD and LSDV outbreaks has been carried out well in accordance with policy objectives. The attitude of policy implementers toward carrying out prevention can be accepted by leaders and also by the public who visit BPTU HPT Padang Mengatas. The implementation of this FMD and LSDV outbreak prevention policy has been carried out well at BPTU HPT Padang Mengatas.